The Influence of Service Quality and Brand Image on Priority Customer Satisfaction at Bank Bengkulu Head Office - Viqi Al Candra; Ahmad Soleh; Tito Irwanto (Penerbit Jurnal Indonesia, 2020)
The purpose of this study was to determine the effect of service quality and brand image on priority customer satisfaction at Bengkulu Bank Head Office. This research is to quantitative descriptive study with the type of data used are primary data through questionnaires. The sample in this study is the priority customers of Bengkulu Bank Head Office, amounting to 110 customers with a sampling method that is purposive sampling. Data analysis methods used include validity, reliability, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the service quality has a positive and significant effect on priority customer satisfaction at Bengkulu Bank Head Office with a regression coefficient of 0.282 and a probability value (sig) 0.000